DYNAMIC EVOLUTION EXOPLANET SYSTEMS, MOVING IN ORBITAL RESONANCES WITH THE ACCOUNT OF SECULAR PERTURBATION FROM N BODIES - Mushailov, B. R.; Chuyas, A. K. (Одеські астрономічні публікації, 2017)
Equations of exoplanet's motion connected with orbital Lindblad resonances with the account of secular terms caused by gravitational non-resonant perturbation are derived. Qualitative researches of orbital evolution modeling exoplanet systems are carried out. Possibility of captures in a resonance is considered at various initial configurations exoplanet systems.